1991
DOI: 10.3758/bf03214309
|View full text |Cite
|
Sign up to set email alerts
|

Judging the relative duration of multimodal short empty time intervals

Abstract: Three experiments address the cause of the different performance levels found in time discrimination of empty intervals with durations near 250 msec. Performance differed according to the kind of sensory modality that marked the intervals. With a procedure in which the type of marker was randomized from trial to trial, it was shown that variability of discrimination judgments could not be attributed entirely to the variability of the criterion on which a judgment was based. Such a randomization slightly affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
100
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 35 publications
18
100
3
1
Order By: Relevance
“…Grondin and Rousseau (1991) found that when a brief beep marked the onset of an interval and a brief light flash marked the offset, the interval was perceived to be longer than when the onset was marked by a light flash and the offset by a beep. Other studies investigating duration judgments reported that simple biases due to perceptual latencies are not sufficient to explain all modality-dependent effects (Ulrich et al, 2006;Wearden, Edwards, Fakhri, & Percival, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Grondin and Rousseau (1991) found that when a brief beep marked the onset of an interval and a brief light flash marked the offset, the interval was perceived to be longer than when the onset was marked by a light flash and the offset by a beep. Other studies investigating duration judgments reported that simple biases due to perceptual latencies are not sufficient to explain all modality-dependent effects (Ulrich et al, 2006;Wearden, Edwards, Fakhri, & Percival, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Following previous work (e.g., Grondin & Rousseau, 1991), the current study uses the biases in temporal perception caused by processing input of different sensory modalities to specify whether there is one modality-independent mechanism or whether multiple mechanisms are involved in processing crossmodal durations. Sensory latencies lead to summative distortion of time.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations